?CLAISEN REARRANGEMENT OF 2'-HYDROXY -4 -METHOXY- 4' -PRENYLOXYCHALCONE - ISLAM, AZlZUL; ANAM, M.RAAQUL; HOSSAIN, M.AMZAD (Biological Sciences - PJSIR, 1994)
Claisen rearrangement of 2'-hydroxy-4-methoxy-4'-prenyloxychalcone (II) using acetic anhydride in dimethyl- aniline gave five compounds and several other minor fractions. The five compounds isolated were viz. 2'-hydroxy-4- methoxy-4",4",5"-trimethyldihydro furano (2",3":4',3') chalcone (III), 2'-hydroxy-4'-acetoxy-4-methoxy-3'-(a,a-di- methylallyl)chalcone(IV),2'-hydroxy-4'-acetoxy-4-methoxy-5'-(a,a-dimethylallyl) chalcone(V),2'-acetoxy-d-rnethoxy- 4'-prenyloxychalcone (VI) and 2'-hydroxy-4'-acetoxy-4-methoxy chalcone (VII). Mild alkaline hydrolysis of Iv gave 2',4'-dihydroxy-4-methoxy-3'-(a,a-dimethylallyl) chalcone (VIII). The products have been characterized by their spectral analysis.